Dynamics of soil microbiome throughout the cultivation life cycle of morel (Morchella sextelata) - Zhang, Chen; Shi, Xiaofei; Zhang, Jiexiong; Zhang, Yesheng; Wang, Wen (Frontiers in Microbiology, 2023)
Although Morchella sextelata (morel) is a well-known, edible and medicinal fungus widely cultivated in China, the dynamics and roles of its soil microbiome during cultivation are unclear. Using rhizosphere soil samples collected throughout the M. sextelata cultivation life cycle, we conducted a high-throughput metagenomic sequencing analysis, with an emphasis on variations in soil microbial composition, characteristic biomarkers, and ecological functions. We found that microbial relative abundance, alpha diversity, and structure varied significantly among fungal growth stages. A total of 47 stage-associated biomarkers were identified through a linear discriminant analysis of effect size. In addition, horizontal comparison of soil microbiomes exhibiting successful and failed primordium formation further confirmed primordium-associated microbes with possible key roles in primordium formation. A microbial function analysis revealed that nutrient metabolism-related pathways were enriched during mycelium and fruiting body stages, whereas the signal transduction pathway was enriched during the primordium stage. This result indicates that diverse microbes are required at different growth stages of M. sextelata. Our research has revealed the dynamic scenario of the soil microbiome throughout the cultivation life cycle of M. sextelata. The high-resolution microbial profiles uncovered in the present study provide novel insights that should contribute to the improvement of morel cultivation using microbial inoculants.